2016
DOI: 10.1080/07420528.2016.1222537
|View full text |Cite
|
Sign up to set email alerts
|

School start time influences melatonin and cortisol levels in children and adolescents – a community-based study

Abstract: School start time influences sleep parameters. Differences between circadian sleep parameters on weekends and weekdays have been associated with obesity, sleep, and psychiatric disorders. Moreover, circadian rhythm dysregulation affects the secretion of some hormones, such as melatonin and cortisol. In the current study, we investigate the effect of school start time on cortisol and melatonin levels in a community sample of Brazilian children and adolescents. This was a cross-sectional study of 454 students (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…According to the chronotype, E-types presented the best exposure pattern, although they were still exposed mostly to indoor bright light. L-types spent most of their daytime underexposed to bright light, while their time in darkness during the night was shorter than for E-types, as has been previously published (Carissimi et al, 2016), probably due to the use of electronic devices (Cain and Gradisar, 2010; Chang et al, 2014; Touitou et al, 2016) until late at night in the L-type group. However, it is still unclear whether differences in voluntary light exposure between chronotypes, which could be explained by the sleep/wake pattern, are the cause or consequence of their circadian phase preference, although differences between them are minimized when both are exposed to natural light–dark cycles (Wright et al, 2013).…”
Section: Discussionsupporting
confidence: 66%
“…According to the chronotype, E-types presented the best exposure pattern, although they were still exposed mostly to indoor bright light. L-types spent most of their daytime underexposed to bright light, while their time in darkness during the night was shorter than for E-types, as has been previously published (Carissimi et al, 2016), probably due to the use of electronic devices (Cain and Gradisar, 2010; Chang et al, 2014; Touitou et al, 2016) until late at night in the L-type group. However, it is still unclear whether differences in voluntary light exposure between chronotypes, which could be explained by the sleep/wake pattern, are the cause or consequence of their circadian phase preference, although differences between them are minimized when both are exposed to natural light–dark cycles (Wright et al, 2013).…”
Section: Discussionsupporting
confidence: 66%
“…There is no pretreatment of samples prior to assay. Melatonin levels in saliva collected at midday in normal children were between 6 and 11 pg/mL with this assay 72,73 while the threshold for calculating DLMO in adults was 10.4 pg/mL. 74 Some recent studies have however reported levels of 0.8-2 pg/mL in adults at 14:00 hours.…”
Section: Saliva Elisamentioning
confidence: 82%
“…However, with the recent body of research on the afternoon school shift [8][9][10][11]22], school start time cannot be considered as a synchronizer, but rather as a social mechanism that will determine the time when adolescents synchronize with the light-dark cycle [30], which is an important physical zeitgeber [31]. Interestingly, in the three studies that assess melatonin in school shifts, results have indicated that light-induced melatonin suppression appears first for adolescents in the morning shift, thus synchronizing their circadian rhythms at different times [32][33][34].…”
Section: Discussionmentioning
confidence: 99%